2019
DOI: 10.1029/2018wr023554
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Dependence of Non‐Fickian Transport in Porous Media

Abstract: In two-phase flow through porous media, the percolating pathways can be hydrodynamically split into the flowing and stagnant regions. The highly variable velocity field in the pore space filled by the carrier fluid leads to significant differences in the transport time scales in the two regions that cannot be explained by the Fickian (Gaussian) advection-dispersion equation. In contrast with the Darcy-scale studies, up to now, relatively limited pore-scale studies have been devoted to the characterization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 50 publications
(81 reference statements)
6
51
1
Order By: Relevance
“…There are alternative methods such as using the MIM ( 22 ) and MRMT ( 23 ) models to estimate the dispersion coefficients. However, they may lead to an incorrect estimation of the fitted parameters due to the inherent assumptions in those models ( 25 ). As an alternative approach, spatial moments ( 51 ) and time moments ( 52 ) can be used to estimate the dispersion coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are alternative methods such as using the MIM ( 22 ) and MRMT ( 23 ) models to estimate the dispersion coefficients. However, they may lead to an incorrect estimation of the fitted parameters due to the inherent assumptions in those models ( 25 ). As an alternative approach, spatial moments ( 51 ) and time moments ( 52 ) can be used to estimate the dispersion coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…None of the commonly used theories, including the mobile–immobile model (MIM) ( 22 ), the multirate mass transfer (MRMT) ( 23 ), and continuous time random walk ( 24 ) models include two-phase flow formulations in their theoretical developments. To date, the capability of such models to match the experimental data using inverse modeling has been tested, but the physical consistency of such models is still open to be evaluated ( 25 , 26 ).…”
mentioning
confidence: 99%
“…Multiphase flow through porous media has a crucial importance in applications as diverse as groundwater resources [1][2][3], geothermal fields [4], chemical transport [5][6][7], gas diffusion in fuel cells [8], oil recovery [9], environmental remediation [10], and CO 2 sequestration [11]. The most important macroscopic parameters that describe multiphase flow through porous media are capillary pressure (P c ) and relative permeability (k r ) [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several research groups started using 2D micromodels in combination with specific optical methods to study tracer propagation in porous media at full [13] and partial saturation [14][15][16][17][18]. All research groups observed non-Gaussian transport and related them to the presence of stagnant zones in the partially saturated porous medium.…”
Section: Introductionmentioning
confidence: 99%